Influence of COVID-19 on the Perception of Academic Self-Efficacy, State Anxiety, and Trait Anxiety in College Students - Alemany-Arrebola, Inmaculada; Rojas-Ruiz, Gloria; Granda-Vera, Juan; Mingorance-Estrada, Ángel Custodio (Frontiers in Psychology, 2020)
The worldwide pandemic situation caused by COVID-19 has led to a state of confinement of the population, which has caused, following consulted research, an increase in stress. Faced with this situation, the Spanish university not only had to adapt to the changes derived from the causes of the pandemic, but also to face a new methodological model - e-learning teaching - for which not always teachers and students are prepared. This can cause an increase in stress due to the uncertainty caused by this time of change. This research analyses the relationship between perceived self-efficacy in the confinement period and the level of trait and state anxiety during COVID-19. 427 students from the University of Granada (Spain) participated in this study. The adaptation of two scales that measure Perceived Academic Self-efficacy and Anxiety (Trait and State) has been applied. The results indicate that there is an inversely proportional relationship between anxiety and self-efficacy; men show the highest perception of self-efficacy, while women have higher scores in Trait Anxiety and State Anxiety; the latter is accentuated when a relative dies.